Pengaduan Masyarakat di Kota Pekanbaru Dalam Perspektif Digital Governance - Arrijal, Abid; Heriyanto, Meyzi; Mayarni, Mayarni (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
The increasing development of digital technology among the community currently means that the Pekanbaru City government, in particular, is utilizing digital technology in the community complaints process called PEKA (PEKAN ADUAN). This research focuses on the Digital Governance perspective in the community complaints process in Pekanbaru City using qualitative methods and data collection techniques in the form of interviews. The PEKA application has become the main platform for the Pekanbaru government to receive various kinds of complaints coming from the public, but in the implementation process it still has various obstacles ranging from network disruption to functions that are not yet optimal and the number of passive users. Digital Governance, which is the benchmark for the implementation of the PEKA application, has prioritized digital concepts in its implementation but still has several obstacles that must be improved.